METACOGNITIVE STRATEGIES AND ACADEMIC PERFORMANCE IN EDUCATION STUDENTS OF THE AMAZON NATIONAL UNIVERSITY OF MADRE DE DIOS - Puma Camargo, María Isabel (2020)
The purpose of this study was to know therelationship between metacognitive strategiesand the development of academic performance instudents of the Professional School of Education ofthe National Amazonian University of Madre de Dios.It is a basic type study, descriptive level and assumesa correlational design. The sample consistedof 61 students from the Professional School ofEducation. The applied techniques were the surveyand the documentary analysis. The instruments:questionnaire and record of qualifications.Metacognitive strategies were evaluated with aninventory of 52 items for all dimensions and theeight categories that are in total. The instrument hadvalidation and reliability using the Cronbach's alphacoefficient with 0.94, 0.61 and 0.71. It was obtainedas a result of the correlation (0.333) betweenmetacognitive strategies and academic performancein students of the Professional School of Educationof the National Amazonian University of Madrede Dios. The conclusion was that there is a weakrelationship between these two variables, whichallows us to affirm that there is no relationship, thatis, there is no correspondence between academicperformance and metagognitive strategies.